2016
DOI: 10.1113/ep085723
|View full text |Cite
|
Sign up to set email alerts
|

Central leptin and resistin combined elicit enhanced central effects on renal sympathetic nerve activity

Abstract: New Findings r What is the central question of this study?Leptin and resistin act centrally to increase renal sympathetic nerve activity (RSNA). We investigated whether a combination of resistin and leptin could induce a greater response than either alone. We also used Fos protein to quantify the number of activated neurons in the brain. r What is the main finding and its importance?A combination of leptin and resistin induced a greater increase in RSNA than either hormone alone. This was correlated with a gre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(29 citation statements)
references
References 41 publications
2
27
0
Order By: Relevance
“…[70] Although the mechanisms of resistin-related kidney injury is less clear, studies have shown that it upregulates expression of Intercellular Adhesion Molecule-1 and vascular cell adhesion molecule-1. [71] In addition, both leptin and resistin enhance renal sympathetic nerve activity,[72] the latter possibly via phosphatidylinositol 3-kinase. [73]…”
Section: Inflammation and Insulin Resistancementioning
confidence: 99%
“…[70] Although the mechanisms of resistin-related kidney injury is less clear, studies have shown that it upregulates expression of Intercellular Adhesion Molecule-1 and vascular cell adhesion molecule-1. [71] In addition, both leptin and resistin enhance renal sympathetic nerve activity,[72] the latter possibly via phosphatidylinositol 3-kinase. [73]…”
Section: Inflammation and Insulin Resistancementioning
confidence: 99%
“…RSNA was amplified using a low‐noise differential amplifier (models ENG 187B and 133; Baker Institute, Melbourne, VIC, Australia), filtered (band pass 100‐1000 Hz), rectified and integrated at 0.5 second intervals. The signals were recorded using a PowerLab data acquisition system (ADInstruments) . The background electrical noise levels were determined post mortem and subtracted from the nerve activity obtained in the anaesthetised rat.…”
Section: Methodsmentioning
confidence: 99%
“…The MAP, HR and RSNA were measured before and for 180 minutes after administration of saline vehicle (n=5; 5 μL), leptin (7 μg in 5 μL; n=4), resistin (7 μg in 5 μL; n=5) and the combination of both resistin and leptin (n=6; leptin was administered 15 minutes after resistin). The doses of each hormone were chosen on the basis of previous studies . At the end of the experiment, the epididymal fat was removed and weighed.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations